International survey-based assessment of the reliability, validity, and interpretability of the TDN grade for neurosurgical adverse events - Terrapon, Alexis; Kälin, Vincens; Zeitlberger, Anna Maria; Weller, Jonathan; Kissling, Cédric; Neidert, Nicolas; Mohme, Malte; El-Garci, Ahmed; Juratli, Tareq A.; Dao Trong, Huy Philip; Stienen, Martin N.; Hostettler, Isabel Charlotte; et al. (Scientific reports, 2025)
Neurosurgical adverse events (AE) are frequent and may have dramatic consequences on quality of life. The lack of a standardized classification of their severity hinders evaluation and improvement of the safety of procedures. The Therapy-Disability-Neurology (TDN) grade, validated in 2021 on 6071 interventions, overcomes limitations of previous grading-systems by addressing the severity of neurologic and disabling AEs. The aim of the current study is to assess the reliability, validity and applicability of the TDN grade. We conducted an online survey involving participants with varying levels of neurosurgical expertise. Participants assessed the TDN grade for 16 case vignettes and reviewed the validity, interpretability, logicality, simplicity, and usefulness of the grading-system. The TDN grade showed substantial inter-rater (α = 0.66) and intra-rater (α = 0.79) reliability. Most participants recommended reporting its separate dimensions, which demonstrated substantial to almost perfect reliability (inter-rater: α = 0.74; intra-rater: α = 0.85). Online calculation tools significantly improved agreement and participants’ scores. The TDN grade was considered fairly useful, very logical, fairly simple to use and interpret, and its separate dimensions were considered a very valid measure of the severity of AEs. Neurosurgical AEs should be systematically reported, and surveyed neurosurgeons recommend the use of the TDN grade along its separate dimensions for this purpose.
Veröffentlicht: 28. Oktober 2025
Gesehen am 02.01.2026